Degradable polyglycolic acid-based conical temporary plugging ball and preparation method thereof

By using polyglycolic acid-based cone-shaped temporary plugging balls, combined with the design of the outer shell and inner core structure, the problems of difficult degradation of existing temporary plugging ball materials and insufficient mechanical strength are solved, achieving efficient plugging and sealing in oil and gas field fracturing operations. Self-degradation improves the development efficiency and economic benefits of oil and gas fields.

CN119331586AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411431416.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-21
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing temporary ball blocking materials are difficult to degrade after the fracturing operation is completed, which increases the operating cost and may cause damage to the formation. At the same time, their degradation speed and mechanical strength are difficult to meet the requirements of complex fracturing processes.

Method used

Poinol -based cone -shaped temporarily blocked balls, combined with the shell and inner core structure, and using polyol acid, polyethylene, ethylene, silane, and methyl tyrite, combined with degradable promoters and antioxidants to prepare to prepare to prepare to prepare out Temporarily blocking the ball with excellent blocking performance and good degradation.

Benefits of technology

Achieve effective blocking cracks in the fracture operation of the oil and gas fields, improve the fracture efficiency, the applicable temperature range is wide, the pressure resistance and stabilization time is long, and it can be degraded by itself after the operation is completed, reducing the pollution of the strata, reducing production costs to production costs , Improve the development efficiency and economic benefits of oil and gas fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083775830000081
    Figure BDA0005083775830000081
  • Figure HDA0005083775840000011
    Figure HDA0005083775840000011
  • Figure HDA0005083775840000012
    Figure HDA0005083775840000012
Patent Text Reader

Abstract

The invention discloses a degradable polyglycolic acid-based conical temporary plugging ball which is in a shape of combining a hemisphere and a cone through a plane end and is provided with a shell and an inner core structure, wherein the shell is prepared from the following raw materials: polyglycolic acid, polyvinyl alcohol, vinyl silane and methacrylic acid; the inner core is prepared from the following raw materials: polyglycolic acid, cellulose ester, a degradation accelerant, a plasticizer, filler and an antioxidant. The temporary plugging ball has excellent plugging performance and good degradability, can effectively plug cracks and improve the fracturing efficiency in oil and gas field fracturing operation, is wide in applicable temperature range, resistant to pressure and long in pressure stabilizing time, can be automatically degraded after operation is completed, can effectively reduce pollution to stratums and complexity of subsequent operation, and has good application prospects. Production cost is reduced, and development efficiency and economic benefits of oil and gas fields are effectively improved; and the related preparation method is simple, convenient and controllable, and can meet the requirements of different stratum conditions and fracturing processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas exploitation, and particularly relates to a degradable polyglycolic acid-based conical temporary plugging ball and a preparation method thereof. Background Art

[0002] As a key means to improve the efficiency of oil and gas field exploitation, fracturing technology is widely used in the production process of oil and gas wells. In the fracturing process, temporary plugging balls are an important auxiliary material used to temporarily plug the cracks that have been opened so that the subsequent fracturing fluid can be diverted to other unfractured formation areas. This diversion technology can effectively improve the fracturing efficiency and increase oil and gas production. However, there are some common problems with existing temporary plugging ball materials: traditional temporary plugging ball materials mainly include polymers, resins, waxes, etc. These materials are difficult to degrade after the fracturing operation is completed, and often require additional measures to remove them, which not only increases the operating cost, but may also cause unnecessary damage to the formation. In addition, the degradation rate and mechanical strength of these materials are often difficult to meet the complex and changeable fracturing process requirements.

[0003] Patent CN102199420A discloses a water-soluble temporary plugging agent, the main components of which are guar gum and aluminum oxide, which will undergo a cross-linking reaction under formation conditions to form a rubber plug with a pressure resistance of about 30MPa, achieving a plugging effect, but it needs to be debonded and unblocked after the fracturing diversion operation. Patent CN103409121A discloses a water-soluble fracturing diversion temporary plugging agent, the core components of which are plant starch, polymer, swelling agent and curing agent; the temporary plugging agent has good solubility, strong adhesion and excellent backflow performance, however, the water-soluble temporary plugging agent also has problems such as incomplete ablation and low pressure resistance. Patent application CN104418999A discloses a temporary plugging agent of a degradable copolyester nanocomposite material, the main components of which are in-situ copolymerization of polyethylene terephthalate (PET) esterification intermediates and inorganic nanoparticles. This material is only suitable for reservoirs above 80°C.

[0004] In recent years, polyglycolic acid (PGA), as a degradable material, has gradually attracted attention due to its excellent biodegradability and environmental friendliness. At present, the industry generally believes that the spherical structure makes the temporary plugging ball easier to move in the fracturing fluid. The symmetry of the sphere can be set at any angle and helps to evenly distribute the pressure on the surface of the sphere. Therefore, the existing polyglycolic acid temporary plugging balls are mostly spherical structures. However, the existing process ignores the deformation and expansion of the blasthole caused by the grinding of the proppant and the erosion of the fracturing fluid. The irregular shape of the blasthole cannot be completely filled during the plugging process, which may lead to poor plugging and affect the plugging effect. The molding of non-spherical temporary plugging balls is more complicated than that of spherical ones, and the pressure bearing requirements are high. At the same time, they need to have sufficient flexibility to adapt to different blasthole diameters and shapes. In addition, polyglycolic acid temporary plugging balls are mostly high-temperature degradable materials, with high requirements for reservoir temperature and a small temperature application range. There are certain limitations in their practical applications. Summary of the invention

[0005] The main purpose of the present invention is to provide a conical PGA temporary plugging ball with excellent plugging performance and good degradability in response to the problems and shortcomings of the prior art, which can effectively plug cracks in oil and gas field fracturing operations and improve fracturing efficiency. It has a wide applicable temperature range, is pressure-resistant, and has a long pressure-stabilizing time. It can degrade itself after the operation is completed (the degradation rate reaches 100%), which can effectively reduce the pollution to the formation and the complexity of subsequent operations, reduce production costs, and improve the development efficiency and economic benefits of oil and gas fields. The preparation method involved is simple and controllable, and can meet the needs of different formation conditions and fracturing processes.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A degradable polyglycolic acid-based conical temporary plugging ball has a morphology of a hemisphere and a cone combined through the plane ends of the two, and has an outer shell and an inner core structure; the shell material includes polyglycolic acid, polyvinyl alcohol, vinyl silane and methacrylic acid; the inner core material includes polyglycolic acid, cellulose ester, a degradation accelerator, a plasticizer, a filler and an antioxidant.

[0008] Furthermore, in the shell raw material, each component and its mass percentage include: 30-40wt% polyglycolic acid, 30-45wt% polyvinyl alcohol, 8-12% vinyl silane, and 15-18% methacrylic acid. The present invention combines polyglycolic acid and polyvinyl alcohol to achieve a balance between biodegradability and good mechanical strength, which not only meets environmental protection requirements but also ensures the durability of the material; at the same time, vinyl silane and methacrylic acid are further introduced as cross-linking agents to enhance the cross-linking density of the material, and can effectively improve the heat resistance and chemical resistance of the obtained shell, so that the temporary plugging ball can remain stable in a complex underground environment.

[0009] Furthermore, in the inner core raw material, the components and their mass percentages include: polyglycolic acid 60-75%, cellulose ester 15-30%, degradation accelerator 0.5-6%, plasticizer 5-15%, filler 5-15%, and antioxidant 2-4%.

[0010] In the above scheme, the polyglycolic acid is a white or light yellow powder with a molecular weight of 300,000-500,000Da, an effective content of ≥96%, and a particle size of 50um-100um; the polyvinyl alcohol is a white or slightly milky yellow powder with a molecular weight of 200,000-400,000Da, a particle size of 50um-100um, and an effective content of ≥95%. The polyglycolic acid and polyvinyl alcohol used have good mechanical strength, toughness and molding properties, can withstand large stress, are not easy to break, and are easy to be made into the desired shape and size by injection molding, extrusion, etc. At the same time, they have good chemical stability, can maintain structural stability in a wide pH range, are not easily affected by acid and alkali environments, and can maintain stable performance for a long time in underground environments.

[0011] In the above scheme, the cellulose ester can be selected from one of cellulose acetate, cellulose acetate butyrate, etc., or a mixture of two of them, which can effectively increase the compressibility and elasticity of the temporary plugging ball, help the temporary plugging ball to better adapt to pores and cracks under high pressure environment, and improve the plugging effect.

[0012] In the above scheme, the degradation accelerator comprises bio-based polyurethane.

[0013] Preferably, the degradation accelerator comprises bio-based polyurethane and amylase; wherein the mass ratio of bio-based polyurethane to amylase is 1:(0.05-0.1).

[0014] Furthermore, the bio-based polyurethane is polycaprolactone-based polyurethane.

[0015] Furthermore, the molecular weight of the bio-based polyurethane is 5000 Da-10000 Da.

[0016] In the above scheme, the bio-based polyurethane introduced in the degradation accelerator can improve the mechanical properties of PGA, making it more stable during the degradation process and avoiding early breakage; it helps to maintain the integrity of the material in the early stage of degradation, and then accelerates the degradation of the entire composite material through the degradation of polyurethane; at the same time, the introduction of polyurethane can increase the sensitivity of the material to hydrolysis, making PGA more susceptible to erosion by water molecules, thereby accelerating its degradation at low temperatures. In addition, bio-based polyurethane can be physically combined with PGA to provide an environment that is more conducive to amylase catalysis. Amylase can accelerate the hydrolysis process of PGA. By designing a combination of materials with different degradation rates, multi-stage degradation can be achieved. This effectively solves the problem of long degradation time of PGA and other fillers at low temperatures, and at the same time adjusts its degradation time under high temperature conditions. The rupture of polymer chains is promoted through different mechanisms, thereby controlling the degradation rate of temporary plugging balls under specific conditions (such as temperature, pressure and pH value).

[0017] In the above scheme, the plasticizer can be selected from one or more of dioctyl sebacate, diethylhexyl phthalate (DEHP), and adipic acid esters. The selected plasticizer is used to increase the plasticity of the polyglycolic acid material, making it easier to process it into the required shape and size during the manufacturing process; at the same time, the hardness of the temporary plugging ball can be adjusted to ensure that the temporary plugging ball is neither too hard to be difficult to seal nor too soft to be effectively sealed.

[0018] In the above scheme, the filler can be selected from one of calcium carbonate, boron carbide, silicon dioxide, etc., which is mainly used to improve the heat resistance, pressure resistance and mechanical strength of the temporary blocking ball, while improving its fluidity and dispersibility, and it itself will not react chemically with other raw materials.

[0019] In the above scheme, the antioxidant can be selected from one of 2,6-di-tert-butyl-p-cresol (BHT), silane coupling agent, ethylenediaminetetraacetic acid (EDTA), etc., which is mainly used to improve the antioxidant properties of the material, especially to improve the thermal stability of the material, so that it is not easy to age in a high temperature environment, and enhance its stability during storage and use.

[0020] Furthermore, in the conical temporary blocking ball, the plane of the hemispherical part is connected to the plane of the conical part, and the shapes and sizes are matched.

[0021] Furthermore, the degradable polyglycolic acid-based conical temporary blocking ball includes a closed outer shell and a core filled inside the outer shell, and the outer wall surfaces of the core body are all in contact with the inner wall surface of the outer shell; the outer shell includes a hollow hemispherical shell and a hollow conical shell, and the open end of the hemispherical shell is connected to the end opening of the conical shell; the hemispherical shell is connected to the core inside the conical shell, and the shape of the core body is consistent with the shape of the corresponding shell.

[0022] Furthermore, the diameter of the hemispherical plane is preferably r=18-32 mm; and the length of the conical generatrix is ​​L=1.2r-1.5r.

[0023] The preparation method of the above-mentioned degradable conical polyglycolic acid conical temporary plugging ball comprises the following steps:

[0024] 1) uniformly mixing the polyglycolic acid, cellulose derivative, degradation accelerator, plasticizer, filler and antioxidant weighed according to the proportion; heating the obtained mixture to a fluid state under stirring conditions to obtain an inner core mixture;

[0025] 2) Injecting the inner core mixture into a conical spherical inner core mold under pressure, cooling naturally under pressure, and cooling to room temperature with water; demoulding to obtain the inner core;

[0026] 3) uniformly mixing the polyglycolic acid, polyvinyl alcohol, vinyl silane and methacrylic acid weighed according to the proportion, and heating them into a uniform liquid state to obtain a shell mixture;

[0027] 4) Fixing the inner core in the conical spherical outer shell mold by fixing pins, wherein the outer side surface of the inner core and the inner cavity wall of the conical spherical outer shell mold form an outer shell casting space; injecting the outer shell mixture (without pressurization), cooling naturally, and cooling to room temperature with water; demoulding, drying, and obtaining the conical temporary plugging ball.

[0028] In the above scheme, the heating temperature used in step 1) is 215-240°C.

[0029] In the above scheme, the pressure used in step 2) is 60-80MPa.

[0030] In the above scheme, the pressure-maintaining natural cooling time in step 2) is 5-8 minutes.

[0031] In the above scheme, the water cooling step in step 2) is controlled for 30-40 minutes.

[0032] In the above scheme, the heating temperature in step 3) is 215-240°C.

[0033] In the above scheme, the natural cooling time in step 4) is 5-8 minutes.

[0034] In the above scheme, the water cooling step in step 4) is controlled for 30-40 minutes.

[0035] In the above scheme, the temperature used in the drying step is 40-60° C. to remove excess solvent and moisture and solidify the shell at the same time.

[0036] Furthermore, the conical spherical inner core mold and the conical spherical outer shell mold include a hemispherical cavity and a conical cavity, wherein the circumference of the opening end of the hemispherical cavity is connected to the circumference of the opening end of the conical cavity, and the sizes thereof match.

[0037] Furthermore, the conical spherical outer shell mold is consistent in shape with the conical spherical inner core mold, and the outer shell mold is a detachable mold. The entire mold consists of two parts. When casting the outer shell, the temporary blocking ball inner core is fixed in the center of the mold by a built-in positioning pin.

[0038] Furthermore, the fixing pin is cylindrical, with a diameter of 0.5-1 mm and a length of 1-2 mm.

[0039] Furthermore, the inner wall of the conical spherical shell mold is provided with a plurality of fixing pins, wherein the inner bottom of the hemispherical cavity is provided with a fixing pin, and the inner wall of the conical cavity is provided with at least two fixing pins at intervals in the circumferential direction.

[0040] Furthermore, the degradable polyglycolic acid conical temporary plugging ball prepared according to the above scheme has vents after demolding, can meet the temporary plugging needs of 60-180℃ reservoirs, has a maximum pressure resistance of 70MPa, a pressure stabilization time of >120min, and can self-degrade after the operation is completed, with a degradation rate of 100%.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The inner core and shell of the temporary plugging ball of the present invention are both made of degradable materials. By optimizing the formula of the inner core and shell, the problems of PGA-based materials being brittle and easy to break under high pressure and high stress environments are effectively improved, and the problem of the slow dissolution rate of polyglycolic acid materials at low temperatures can be effectively solved, which greatly increases the application temperature range of the PGA temporary plugging ball reservoir;

[0043] (2) Compared with the existing bullet-shaped, truncated cone-shaped, rugby-shaped and other irregular temporary plugging balls, the conical design of the present invention is easier to position in the blasthole, avoiding rolling or movement problems, and providing better stability, especially in inclined or vertical wellbores, which helps to keep the temporary plugging ball in place. At the same time, because the diameter of the conical part gradually increases with the generatrix, it can adapt to blastholes of various diameters and different degrees of deformation, fit the well wall more closely, and improve the plugging efficiency. At the same time, the conical structure helps to guide the fluid to disperse around, thereby improving the plugging effect.

[0044] (3) Compared with the traditional polyglycolic acid temporary plugging balls, the modified polyglycolic acid temporary plugging balls of the present invention have a wider applicable temperature range. By changing the raw material ratio, temporary plugging balls suitable for a temperature series of 60-180°C can be formed, and the compressive strength can reach 60MPa. At the same time, the preparation process of the temporary plugging balls is simple, and they are easy to mass produce, thereby reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a diagram of the temporary ball blocking structure;

[0046] Figure 2 Schematic diagram of the mold structure used in the embodiment, wherein the left figure is a schematic diagram of the shell mold structure, and 1 in the figure is a positioning pin; the right figure is a schematic diagram of the fixation of the inner core in the shell mold.

[0047] Figure 3 It is a schematic diagram of the structure of the positioning pin. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The methods described in the examples are all conventional methods unless otherwise specified; the reagents used are all commercially available unless otherwise specified.

[0050] In the following examples, the bio-based polyurethane is polycaprolactone-based polyurethane (CLPU) with a molecular weight of 5000Da-10000Da, and the manufacturer is BASF SE.

[0051] The molecular weight of the cellulose acetate used is 100,000-150,000Da, and the molecular weight of the cellulose acetate butyrate is 100,000-200,000Da, which are provided by Jiangsu Pules Biotechnology Co., Ltd.

[0052] Example 1

[0053] A degradable polyglycolic acid-based conical temporary plugging ball (schematic diagram of the structure is shown in Figure 1 ), the core components and their mass percentages are: polyglycolic acid 60g (molecular weight 400000Da), cellulose acetate 15g, bio-based polyurethane 2.7g, amylase 0.27g, dioctyl sebacate 5g, diethylhexyl phthalate (DEHP) 5g, silicon dioxide 10g, ethylenediaminetetraacetic acid (EDTA) 2g; the shell components and their mass percentages are: polyglycolic acid 30g (molecular weight 400000Da), polyvinyl alcohol 45g (molecular weight 300000Da), vinyl silane 10g, methacrylic acid 15g;

[0054] The preparation method of the temporary blocking ball comprises the following steps:

[0055] The polyglycolic acid, cellulose acetate, bio-based polyurethane, dioctyl sebacate, diethylhexyl phthalate (DEHP), silicon dioxide, and ethylenediaminetetraacetic acid weighed in proportion are mixed uniformly; the obtained mixture is heated to 220° C., and while heating, a mixer is used to fully mix the mixture to ensure the uniformity of the mixture, thereby obtaining an inner core mixture (heat preservation);

[0056] Select a conical ball inner core mold with a hemispherical inner diameter r=17mm and a generatrix length=20.4mm, apply a layer of lubricating oil on the inner surface of the mold, and preheat it to above 200°C; under a pressure of 70MPa, inject the obtained inner core mixture into the preheated No. 1 conical ball inner core mold; maintain the pressure, cool naturally in the mold for 5-8min, and then use circulating coolant (such as water) to water-cool the mold. After the temperature drops to room temperature in 30min, open the mold to take out the inner core, check its appearance and quality, ensure that the inner core surface is smooth and defect-free, and then carry out subsequent processing;

[0057] (3) Mixing polyglycolic acid, polyvinyl alcohol, vinyl silane, and methacrylic acid weighed in proportion and heating to 220±5° C. to dissolve and mix them uniformly to obtain a shell mixture;

[0058] (4) Select a shell mold with a hemispherical inner diameter r = 18 mm and a busbar length = 21.6 mm (see Figure 2 ), fix the inner core at the center of the outer shell mold by a cylindrical positioning pin 1, inject the outer shell mixture into the annular space of the inner cavity of the irregular conical spherical outer shell mold to form an outer shell around the inner core; after natural cooling for 5 minutes, use a circulating coolant (such as water) to water-cool the mold and reduce the temperature to room temperature within 30-40 minutes;

[0059] (5) demoulding and drying at a constant temperature of 40° C. to obtain the degradable polyglycolic acid-based conical temporary plugging ball, with three vent holes at the positions of the fixing pins around the spherical surface.

[0060] Example 2

[0061] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0062] The components of the inner core and their mass percentages are: 67 g of polyglycolic acid (molecular weight 400,000 Da), 15 g of cellulose acetate butyrate, 3.8 g of bio-based polyurethane, 0.2 g of amylase, 5 g of adipate, 7 g of boron carbide, and 2 g of 2,6-di-tert-butyl-p-cresol (BHT);

[0063] The shell components and their mass percentages are: polyglycolic acid 34g (molecular weight 400000Da), polyvinyl alcohol 40g (molecular weight 400000Da), vinyl silane 8g, methacrylic acid 18g

[0064] Example 3

[0065] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0066] The core components and their mass percentages are: polyglycolic acid 70g (molecular weight 300000Da), cellulose acetate 10g, cellulose acetate butyrate 5g, bio-based polyurethane 1.8g, amylase 0.2g, diethylhexyl phthalate (DEHP) 3g, adipate 2g, boron carbide 5g, 2,6-di-tert-butyl-p-cresol (BHT) 3g;

[0067] The shell components and their mass percentages are: 40 g of polyglycolic acid (molecular weight 300,000 Da), 30 g of polyvinyl alcohol (molecular weight 400,000 Da), 12 g of vinyl silane, and 18 g of methacrylic acid.

[0068] Comparative Example 1

[0069] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0070] The core components and their mass percentages are: polyglycolic acid 70g (molecular weight 300000Da), cellulose nitrate 5g, cellulose phosphate 10g, bio-based polyurethane 1.8g, amylase 0.2g, diethylhexyl phthalate (DEHP) 3g, adipate 2g, boron carbide 5g, 2,6-di-tert-butyl-p-cresol (BHT) 3g;

[0071] The shell components and their mass percentages are: 40 g of polyglycolic acid (molecular weight 300,000 Da), 30 g of polyvinyl alcohol (molecular weight 400,000 Da), 12 g of vinyl silane, and 18 g of methacrylic acid.

[0072] Comparative Example 2

[0073] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0074] The components of the inner core and their mass percentages are: polyglycolic acid 70 g (molecular weight 300000 Da), cellulose acetate 10 g, cellulose acetate butyrate 5 g, diethylhexyl phthalate (DEHP) 3 g, adipate 2 g, boron carbide 5 g, 2,6-di-tert-butyl-p-cresol (BHT) 3 g;

[0075] The shell components and their mass percentages are: 40 g of polyglycolic acid (molecular weight 300,000 Da), 30 g of polyvinyl alcohol (molecular weight 400,000 Da), 12 g of vinyl silane, and 18 g of methacrylic acid.

[0076] Comparative Example 3

[0077] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0078] The core components and their mass percentages are: polyvinyl alcohol 70g (molecular weight 50000Da), cellulose acetate 10g, cellulose acetate butyrate 5g, bio-based polyurethane 1.8g, amylase 0.2g, diethylhexyl phthalate (DEHP) 3g, adipate 2g, boron carbide 5g, 2,6-di-tert-butyl-p-cresol (BHT) 3g;

[0079] The shell components and their mass percentages are: 40 g of polyglycolic acid (molecular weight 300,000 Da), 30 g of polyvinyl alcohol (molecular weight 400,000 Da), 12 g of vinyl silane, and 18 g of methacrylic acid.

[0080] Comparative Example 4

[0081] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0082] The core components and their mass percentages are: polyglycolic acid 70g (molecular weight 300000Da), cellulose acetate 10g, cellulose acetate butyrate 5g, bio-based polyurethane 1.8g, amylase 0.2g, diethylhexyl phthalate (DEHP) 3g, adipate 2g, boron carbide 5g, 2,6-di-tert-butyl-p-cresol (BHT) 3g;

[0083] The shell components and their mass percentages are: 40 g of polyglycolic acid (molecular weight 50,000 Da), 30 g of polyvinyl alcohol (molecular weight 50,000 Da), 12 g of vinyl silane, and 18 g of methacrylic acid.

[0084] Comparative Example 5

[0085] A degradable polyglycolic acid-based conical temporary plugging ball, the preparation method of which is substantially the same as that of Example 1, except that:

[0086] The components of the inner core and their mass percentages are: polyglycolic acid 70 g (molecular weight 300000 Da), cellulose acetate 10 g, cellulose acetate butyrate 5 g, amylase 2 g, diethylhexyl phthalate (DEHP) 3 g, adipate 2 g, boron carbide 5 g, 2,6-di-tert-butyl-p-cresol (BHT) 3 g;

[0087] The shell components and their mass percentages are: 40 g of polyglycolic acid (molecular weight 300,000 Da), 30 g of polyvinyl alcohol (molecular weight 400,000 Da), 12 g of vinyl silane, and 18 g of methacrylic acid.

[0088] The temporary plugging balls obtained in the embodiment and the comparative example were tested for key indicators such as pressure resistance, temperature resistance and solubility, and the results are shown in Table 1.

[0089] Table 1 Performance test results of temporary plugging agents obtained in Examples and Comparative Examples Experimental results

[0090]

[0091]

[0092] The above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Although the above embodiments describe the present invention in detail, relevant technical personnel in the field should understand that the present invention can be modified or equivalently replaced, but any modification and partial replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A degradable polyglycolic acid-based conical temporary plugging ball, characterized in that: It has a shape of a hemisphere and a cone with a flat end, and has an outer shell and an inner core structure; the shell material includes polyglycolic acid, polyvinyl alcohol, vinyl silane and methacrylic acid; the inner core material includes polyglycolic acid, cellulose ester, a degradation accelerator, a plasticizer, a filler and an antioxidant.

2. The degradable polyglycolic acid-based conical temporary plugging ball according to claim 1, characterized in that: The components and their mass percentages in the shell raw material include: 30-40wt% of polyglycolic acid, 30-45wt% of polyvinyl alcohol, 8-12% of vinyl silane, and 15-18% of methacrylic acid.

3. The degradable polyglycolic acid-based conical temporary plugging ball according to claim 1, characterized in that: Ester 15-30%, degradation accelerator 0.5-6%, plasticizer 5-15%, filler 5-15%, antioxidant 2-4%.

4. The degradable polyglycolic acid-based conical temporary plugging ball according to claim 1, characterized in that: The cellulose ester is one of cellulose acetate and cellulose acetate butyrate, or a mixture of the two.

5. The degradable polyglycolic acid-based conical temporary plugging ball according to claim 1, characterized in that: The degradation accelerator is one or both of bio-based polyurethane and amylase.

6. The degradable polyglycolic acid-based conical temporary plugging ball according to claim 1, characterized in that: The plasticizer is one or more of dioctyl sebacate, diethylhexyl phthalate, and adipic acid ester.

7. The degradable polyglycolic acid-based conical temporary plugging ball according to claim 1, characterized in that: The filler is one of calcium carbonate, boron carbide and silicon dioxide; the antioxidant is one of 2,6-di-tert-butyl-p-cresol, silane coupling agent and ethylenediaminetetraacetic acid.

8. The method for preparing the degradable conical polyglycolic acid conical temporary plugging ball according to any one of claims 1 to 7, characterized in that: The steps include: 1) uniformly mixing the polyglycolic acid, cellulose derivative, degradation accelerator, plasticizer, filler and antioxidant weighed according to the proportion; heating the obtained mixture to a fluid state under stirring conditions to obtain an inner core mixture; 2) Injecting the inner core mixture into a conical spherical inner core mold under pressure, cooling naturally under pressure, and cooling to room temperature with water; demoulding to obtain the inner core; 3) uniformly mixing the polyglycolic acid, polyvinyl alcohol, vinyl silane and methacrylic acid weighed according to the proportion, and heating them into a uniform liquid state to obtain a shell mixture; 4) Fixing the inner core in the conical spherical outer shell mold by fixing pins, wherein the outer side surface of the inner core and the inner cavity wall of the conical spherical outer shell mold form an outer shell casting space; injecting the outer shell mixture, cooling naturally, and water cooling to room temperature; demoulding, drying, and obtaining the conical temporary plugging ball.

9. The preparation method according to claim 8, characterized in that: The heating temperature used in step 1) is 215-240°C; the heating temperature in step 3) is 215-240°C.

10. The preparation method according to claim 8, characterized in that: Step 2) The water cooling step lasts for 30-40 minutes; Step 4) The water cooling step lasts for 30-40 minutes.

Citation Information

Patent Citations

  • Temporary plugging agent for staged fracturing of horizontal well and preparation method thereof

    CN102199420A

  • Water-soluble temporary plugging diversion agent for fracturing and preparation method thereof

    CN103409121A

  • Biodegradable copolyester nanometer composite material and temporary plugging agent prepared from biodegradable copolyester nanometer composite material

    CN104418999A

  • Dissoluble degrading temporary blocking ball for temporarily blocking perforation blast hole and preparation method thereof

    CN107573913A

  • Acid-resistant temporary plugging agent and preparation method thereof

    CN112940697A